An examination of the random walk model and technical trading rules in the Malaysian stock market / Lai Ming Ming; Balachandher, K. Guru and Fauzias Mat Nor - Lai, Ming Ming; Balachandher, K. Guru (Accounting Research Institute (ARI) & Faculty of Accountancy, 2007)
This paper examines the predictability of technical trading rules on the daily returns of the Kuala Lumpur Stock Exchange Composite Index for the full sample period from January 1977 to December 1999 which includes both bullish and bearish periods. The methodology employed includes both the variance ratio test and moving average rules. The results indicate nonrandomness of successive price changes. The degree of predictability is supported as the trading rules examined indicate technical attractiveness with the presence of transaction costs